A Newly Discovered Genetic Disorder Associated With Life-Threatening Aortic Disease in a 6-Year-Old Boy - Mohanad Hamandi MD; Madison L. Bolin; Joy Fan; Allison T. Lanfear; Seth K. Woolbert; Ronald D. Baxter MD; J. Michael DiMaio MD; William T. Brinkman MD (SAGE Publishing, 2020)
Aortic aneurysms in children are rare and when present are usually caused by a connective tissue disorder. In this article, we present a case of multiple aortic aneurysms in an adolescent with a novel finding of a gene variation that is associated with aortic disease.